2016
DOI: 10.1039/c5cp05268h
|View full text |Cite
|
Sign up to set email alerts
|

The roles of different titanium species in TS-1 zeolite in propylene epoxidation studied by in situ UV Raman spectroscopy

Abstract: Titanium silicalite (TS-1) zeolites with different titanium species were synthesized and characterized by ultraviolet (UV)-Raman, ultraviolet visible (UV-Vis) diffuse reflectance spectroscopies and by the NH3 temperature programmed desorption (NH3-TPD) method. The roles of different titanium species in TS-1 samples have been investigated by gas chromatography-Raman spectrometry (GC-Raman) during the propylene epoxidation process. For the first time, a positive correlation was found among the concentration of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 121 publications
(77 citation statements)
references
References 38 publications
4
73
0
Order By: Relevance
“…It was found that the acidity of the amorphous Ti species is stronger than that of the anatase TiO 2 , which leads to undesired side reaction. 13 For the low-cost TS-1 zeolite, the distribution of the titanium species is more complicated. Therefore, to improve its catalytic properties, a systematic study on the distribution and the roles of the different titanium species, before and aer the post-treatment, are highly required to be known.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…It was found that the acidity of the amorphous Ti species is stronger than that of the anatase TiO 2 , which leads to undesired side reaction. 13 For the low-cost TS-1 zeolite, the distribution of the titanium species is more complicated. Therefore, to improve its catalytic properties, a systematic study on the distribution and the roles of the different titanium species, before and aer the post-treatment, are highly required to be known.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 It was accepted that the isolated titanium species in the framework of the TS-1 zeolite is the active site for the selective oxidation. The non-framework Ti species is harmful for the epoxidation reactions.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations